1998
DOI: 10.1097/00005768-199804000-00006
|View full text |Cite
|
Sign up to set email alerts
|

High frequency diaphragmatic fatigue detected with paired stimuli in humans

Abstract: We interpret these data to mean that high frequency fatigue as well as low frequency fatigue were present in the diaphragm after intense whole body endurance exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…The inconsistent decreases in transdiaphragmatic twitch pressure after maximal incremental exercise (−15% across stimulus frequencies) were less than the reductions typically observed after sustained, high-intensity exercise (−20 to 32%) (Johnson et al 1993;Babcock et al 1998). That maximal incremental exercise did not elicit significant diaphragm fatigue points to the critical importance of exercise duration and intensity in defining the fatigability of the diaphragm and its role in exercise performance.…”
Section: Inspiratory Muscle Fatigue-mentioning
confidence: 89%
See 2 more Smart Citations
“…The inconsistent decreases in transdiaphragmatic twitch pressure after maximal incremental exercise (−15% across stimulus frequencies) were less than the reductions typically observed after sustained, high-intensity exercise (−20 to 32%) (Johnson et al 1993;Babcock et al 1998). That maximal incremental exercise did not elicit significant diaphragm fatigue points to the critical importance of exercise duration and intensity in defining the fatigability of the diaphragm and its role in exercise performance.…”
Section: Inspiratory Muscle Fatigue-mentioning
confidence: 89%
“…We used single (nonpotentiated and potentiated) and paired stimuli (interstimulus intervals: 100 ms [10 Hz], 20 ms [50 Hz] and 10 ms [100 Hz]) to discriminate between low and high frequency fatigue (Yan et al 1993;Polkey et al 1997;Babcock et al 1998). For paired stimuli the two stimulators were synchronized by a separate module (BiStim Module, Jali Medical Inc., Newton, MA).…”
Section: Diaphragm Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…In normoxia, it has been shown that a relative exercise intensity of Ͼ85% of V O 2max sustained to exhaustion is necessary to elicit diaphragm fatigue (11,40). Furthermore, a work rate Ͼ80% of V O 2max is needed in order for the relief of inspiratory muscle work to significantly increase limb blood flow and limb O 2 transport (66).…”
Section: Conditions Under Which Respiratory Muscle Work Might Be Expementioning
confidence: 99%
“…We used magnetic stimulation of the femoral nerve to determine a force-frequency relationship for the quadriceps (2,30,33,34,40). The technique was highly reproducible between and within days, which was critical to our ability to detect systematic effects of exercise-induced hypoxemia on quadriceps fatigue.…”
Section: Technical Considerationsmentioning
confidence: 99%